MRIM (Multiple Representation-Based Interactive Multimedia): Is it Good to Improve Students’ Scientific Literacy? - Arief Muliandi; Nur Endah Susilowati; Siti Rahmah; Sri Wahyuni; Dadi Rusdiana (U-Teach: Journal Education of Young Physics Teacher, 2021)
The low scientific literacy of Indonesian students attracts the attention of Indonesian education practitioners to continue researching the right solution to overcome it. With the help of multi-representation interactive multimedia, this research facilitated students to learn actively and independently. The aim of this research was to develop multi representation-based interactive multimedia (MRIM) to improve students' scientific literacy skills. The research method is research and development with 4D model (define, design, develop, and disseminate), and data analysis using Paired t-test. The define stage for problem identification and analyzing needs, we involved a sample of 30 students from 8th grade and 2 science teachers. At the design stage, a multimedia framework and scientific literacy instruments were created. In the develop stage, multimedia was tested on 1 lecturer as a reviewer, and 3 teachers, and then the media was tested on a small group, consisted of 7 students of 7th grade of SMPQT Al-Hamidiyah with random selection. And at the disseminate stage, all data that has been processed is then written in the form of articles which will then be published. The results of the expert judgment test stated that the multimedia is feasible to use, while the small group test results showed that this multimedia can improve students' scientific literacy skills with a significance value of 0.000 <0.05 (based on the results of the paired t-test). In conclusion, this interactive multimedia is very suitable for use in learning and can improve students' scientific literacy skills